Immunolocalization in three dimensions: immunogold staining of cytoskeletal and nuclear matrix proteins in resinless electron microscopy sections. - Nickerson, J A (1990)
We describe two methods for staining resinless thin sections with antibodies and gold-conjugated second antibodies. Immunolocalization of specific proteins is a powerful tool for cell structure studies but current techniques do not develop its full potential. Immunofluorescence provides only low-resolution localization, whereas conventional thin-section electron microscopy images and immunostains only the section surface. Resinless sections of extracted cell structures offer a simple and effective means of immuno-electron microscopy. Without embedding plastic or soluble proteins, the cell cytostructure produces high-contrast, three-dimensional images. Resinless sections of detergent-extracted cells are prepared by embedding in diethylene glycol distearate, sectioning, and removing diethylene glycol distearate before microscopy. In the first method of immunostaining, extracted cells were fixed and stained with antibodies before embedment, sectioning, removal of the embedding resin, and critical point drying. In the postembedment method, the sample was embedded and sectioned, the diethylene glycol distearate was removed, and the sample was rehydrated before antibody staining. With these techniques, specific proteins were localized with high resolution throughout the entire section. Stereoscopic micrographs of resinless sections revealed the precise localization of specific cytoskeleton and nuclear matrix proteins in three dimensions with unprecedented clarity.